Co-valorization of lignin and waste polyethylene terephthalate (PET) via Fe/β-zeolite-catalyzed tandem depolymerization - Chang Li; Shihai Yang; Hongzhi Luo; Haiping Chen; Yishuang Wang; Yichen Chen; Chuannan Nie; Defang Liang; Mingqiang Chen (Chemical Engineering Journal, 2026)

Antibacterial mechanisms of magnolol against Streptococcus agalactiae and immunomodulatory effects in Schizothorax prenanti - Yilin Wang; Kun Peng; Longjun Deng; Yihao Wang; Qibin Jiang; Tiancai Li; Ping Ouyang; Defang Chen; Xiaoli Huang; Yi Geng (Fish & Shellfish Immunology, 2026)

Micro-macro coupled dynamics and bidirectional predictive modeling of vertical stirred mills using DEM-CFD - Wenda Yu; Jiaxuan Cui; Jinlu Hu; Yao Li; Defang Zou (Minerals Engineering, 2026)

Cationic nickel sites coupled with oxygen vacancy for boosting dry reforming of methane over CO2-treated Sm-modified Ni/MCM-41 - Yishuang Wang; Suyu Wang; Defang Liang; Mingqiang Chen; Tao Yang; Liwen Shi; Chang Li; Jun Wang; Haosheng Xin; Peng Wang; Zhuowu Men; Liang Yuan (Chemical Engineering Journal, 2026)

Radical-mediated decomposition and polymerization for rapid humification and pollutant removal of livestock manure - Mengyu Ma; Hengtong Liu; Jianing Gai; Wenhan Liu; Yanqin Wang; Lushan Wang; Defang Ma; Rutao Liu; Qian Li (Bioresource Technology, 2026)

Dietary exposure to 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47) induces liver necroptosis via JAK3/STAT4 pathway in carp (Cyprinus carpio) - Mengbin Yuan; Nian Han; Shuhuang Chen; Changyuan Li; Shiqi Li; Buwen Tian; Ni Tang; Bo Zhou; Xue Du; Defang Chen; Zhiqiong Li; Xin Zhang (Aquatic Toxicology, 2026)

Dissecting corneal drug permeability under experimental variability and drug cold-start challenges via hybrid machine learning - Shuya Xu; Nannan Wang; Yong Tao; Chihua Li; He Song; Defang Ouyang (Drug Delivery and Translational Research, 2026)

Secondary structure-regulated self-assembly of zein: mechanisms, morphological regulation, and adsorptive removal of pollutants in wastewater - Defang Teng; Weitai Sun; Yiyou Liu; Xiaolu Ma; Bo Yang; Wei Li; Zengge Guo (Journal of Environmental Sciences, 2026)

Achieving 9.11 GHz broadband microwave absorption in CeO₂/Sn@C composites via Sn doping and structural modulation - Yecheng Qiu; Hao Ma; Jinhua Du; Wei Li; Xiaolong Wang; Yizhe Tian; Xu Mu; Defang Duan; Yingnan Wang (Chemical Engineering Journal, 2026)

A Process-based classification of meteorological mechanisms influencing airborne pollen concentrations in northern and northwestern China - Zining Yuan; Huiyu Ning; Xingqin An; Qingyu Wei; Defang Wei; Wenqiao Xue; Ning He; Lina Di; Xinli Yang; Ying Li; Rui Li; Hongjian Li; et al. (Atmospheric Research, 2026)

Chronic ammonia-N exposure impairs the intestinal health of the Siberian sturgeon (Acipenser baerii Brandt): through the pathways of oxidative stress, tight junction proteins, inflammatory factors, and intestinal microbiota - Huimin Sun; Qiang Hu; Yujie Huang; Siqi Zhao; Guangwei Cao; Zhizhen Zhang; Fei Wang; Defang Chen; Zhiqiong Li; Xin Zhang (Fish & Shellfish Immunology, 2026)

Genome-wide characterization of the caspase family genes in different sturgeons: Insights into lineage-specific expansion and immune responses - Hao Zhu; Yi Geng; Zhiqiong Li; Defang Chen (Fish & Shellfish Immunology, 2026)

Dual-stimuli magnetic drug nanoparticles for chemoimmunotherapy: Magnetically driven, charge-reversal enhanced tumour penetration and pH-triggered drug release - Xue Feng; Hongdi Wang; Yuxiang Xue; Nurbanu Ozgultekin; Takanori Kitamura; Jin Li; Defang Ouyang; Guangyu Zhu; Guangzhao Mao; Bin-Zhi Qian; Xianfeng Chen (Chemical Engineering Journal, 2026)

Integrated Experimental and Molecular Modeling Techniques to Investigate the Buffer Effects on Glucagon Stability - Zi-Ting Xu; Bogang Li; Jiayin Deng; Jia-Yi Lv; Defang Ouyang; Wei-Jie Fang (Pharmaceutical Research, 2026)

Dendritic mesoporous silica nanospheres supported NiCo bimetallic catalysts for efficient cleavage of CC with formic acid for lignin depolymerization - Chang Li; Hongzhi Luo; Chunhui Zhou; Haiping Chen; Yishuang Wang; Shihai Yang; Chuannan Nie; Defang Liang; Mingqiang Chen (Chemical Engineering Journal, 2026)

LncRNA AC098613.1 promotes acute myeloid leukemia cell differentiation through CDC5L/ADAP1/NRD1 axis - Qingling Jiang; Xiaoting Wang; Hang Yao; Jince Wang; Peiyu Tang; Mingpeng Liang; Zhaohai Pan; Bohan Li; Chunhua Lin; Qinxuan Wu; Qi Wang; Qiusheng Zheng; et al. (Apoptosis, 2026)

The bactericidal efficacy of carvacrol against drug-resistant Streptococcus iniae and its protective effects on channel catfish (Ictalurus punctatus) - Lizi Yin; Minmin Wang; Jianing Wu; Xiaonan Li; Fen Chen; Bowen Liu; Yi Geng; Xiaoli Huang; Defang Chen; Ping Ouyang (Aquaculture, 2026)

Effects of different drying methods on the physicochemical properties, antioxidant activity and gut microbiota fermentation behaviours of polysaccharides from Schizophyllum commune - Lihong Fan; Chaomin Yin; Haina Ma; Jing Wen; Maofen Yi; Zhenshun Li; Xiuzhi Fan; Defang Shi; Zhicheng Huang; Jianhui Qiu; Hong Gao (Food Research International, 2026)

Comparison of physicochemical properties of water- and alkaline-extracted polysaccharides from Schizophyllum commune and their anti-obesogenic effects in vivo - Chen Li; Chaomin Yin; Jiangtao Li; Jing Wen; Lihong Fan; Haina Ma; Xiuzhi Fan; Defang Shi; Wei Yu; Jianhui Qiu; Hong Gao (Food Chemistry, 2026)

Schizophyllum commune polysaccharide ameliorates diet-induced obesity by regulating the Faecalibaculum rodentium/indole-3-lactic acid/microRNA axis - Chaomin Yin; Chen Li; Xiuzhi Fan; Defang Shi; Jiangtao Li; Jianhui Qiu; Fen Yao; Wei Yu; Hong Gao (Carbohydrate Polymers, 2026)

Genome-transcriptome co-analysis identifies members and molecular characteristics of the TRAF gene family in Siberian sturgeon (Acipenser baerii) - Shaotong Dai; Hao Zhu; Defang Chen; Yinqiu Chen; Jiawen Zhou; Zhiqian Jin; Wei Long; Xin Zhang; Zhiqiong Li (Fish & Shellfish Immunology, 2025)

Sodium promotion in hydrothermal carbon-derived Fe/Fe₃C catalysts enables reversal of olefin-paraffin selectivity in Fischer-Tropsch synthesis - Mingqiang Chen; Xuemei Shen; Chang Li; Yishuang Wang; Defang Liang; Quan Wang; Chunyue Cheng; Chuannan Nie; Jiawen Hu (Chemical Engineering Journal, 2025)

Gene expression of long non-coding RNAs and messenger RNAs in Varroa destructor mites exposed to essential oil of camphor leaves - Siyi Shen; Meng Li; Tongyu Dong; Kai Xu; Lili Wu; Kang Wang; Defang Niu; Qingsheng Niu; Ting Ji; Zhi Wang; Zheguang Lin (Experimental and Applied Acarology, 2025)

Chronic dietary exposure to BDE-47 can induce inflammatory responses in the brain of common carp (Cyprinus carpio) and further trigger neurotoxicity through the 5-HT pathway - Huimin Sun; Youlian Liu; Yujie Huang; Mengbin Yuan; Zujun Ye; Rong Yang; Fuqiang Sha; Ni Tang; Bo Zhou; Defang Chen; Zhiqiong Li; Xin Zhang (Science of The Total Environment, 2025)

Concentrated mannan oligosaccharide supports grass carp (Ctenopharyngodon idellus) health during Ichthyophthirius multifiliis infection: Histopathological and immunological study - Fulong Li; Ming Xu; Baipeng Chen; Senyue Liu; Yanhao Cao; Yufan Zhang; Gang Lin; Ping Ouyang; Defang Chen; Yi Geng; Xiaoli Huang (Aquaculture, 2025)

Optimization of attapulgite acidification temperature in NiCo/attapulgite for dry reforming of methane - Yishuang Wang; Defang Liang; Quan Wang; Liwen Shi; Weiqing Xu; Chang Li; Mingqiang Chen; Peng Wang; Zhuowu Men; Jun Wang; Liang Yuan (Chemical Engineering Journal, 2025)

Oxygen vacancies-mediated the peracetic acid activation to selectively generate 1O2 for water decontamination - Yi Chen; Qian Li; Ruidian Su; Yixuan Gao; Ning An; Yu Rong; Xing Xu; Defang Ma; Yan Wang; Baoyu Gao (Water Research, 2025)

Study on the correlation between Flavobacterium columnare infection and gill injury in Largemouth bass (Micropterus salmoides) and the protective effect of Enoxolone - Chen Li; Yunshan Qiu; Lin Luo; Xinnan Zhou; Hongli Liu; Ping Ouyang; Yi Geng; Defang Chen; Xiaoli Huang (Fish & Shellfish Immunology, 2025)

The pathological characteristics at different stages and early diagnosis by duplex PCR of Nocardia seriolae disease in largemouth bass (Micropterus salmoides) - Xinnan Zhou; Yunshan Qiu; Chen Li; Ya Huang; Ping Ouyang; Defang Chen; Yi Geng; Xiaoli Huang (Aquaculture, 2025)

Spatially-confined removal of intracellular antibiotic resistance genes via electrochemical membranes: Influence of pore size on electrical stimulation and exogenous reactive oxygen species oxidation - Yunxin Zhang; Jiajun Lu; Shiping Xu; Defang Ma; Qian Li; Zhining Wang; Baoyu Gao; Yan Wang (Journal of Hazardous Materials, 2025)

New insights on the protection of endangered aquatic species: Embryotoxicity effects of 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47) via integrin-mediated oxidative stress and inflammatory pathways in Siberian sturgeon, Acipenser baerii - Changyuan Li; Mengbin Yuan; Jiayi Du; Ziqing Chen; Shuhuang Chen; Xiaokun Ji; Ni Tang; Defang Chen; Zhiqiong Li; Xin Zhang (Fish & Shellfish Immunology, 2025)

Transcriptome analysis reveals the mechanism of cortisol through GR regulating the expression of inflammatory cytokines in Siberian sturgeon (Acipenser baerii) after LPS treatment in vitro - Peng Tang; Yinqiu Chen; Defang Chen; Hao Zhu; Shaotong Dai; Jiawen Zhou; Xin Zhang; Xiaoli Huang; Ping Ouyang; Yi Geng; Zhiqiong Li (Fish & Shellfish Immunology, 2025)

Evaluation of the antibacterial activity and mechanism of cannabigerol against drug-resistant Streptococcus iniae in vitro - Jianing Wu; Minmin Wang; Tingke He; Xiaonan Li; Bowen Liu; Fen Chen; Yi Geng; Weiming Lai; Xiaoli Huang; Defang Chen; Ping Ouyang (Archives of Microbiology, 2025)

Combining High-Throughput Screening and Machine Learning to Predict the Formation of Both Binary and Ternary Amorphous Solid Dispersion Formulations for Early Drug Discovery and Development - Tianshu Lu; Yiyang Wu; Ping Xiong; Hao Zhong; Yang Ding; Haifeng Li; Defang Ouyang (Pharmaceutical Research, 2025)

Silencing LINC01547 induces hepatocellular carcinoma cell apoptosis and metastasis inhibition via the ADAR1/FAK and miR-146b-5p/RAC1 axes - Dan Wang; Huijie Zhao; Ying Zhao; Xuejing An; Chuanqin Shi; Zhaohai Pan; Qiusheng Zheng; Xin Wang; Jun Lu; Defang Li (Apoptosis, 2025)

Elimination of antimicrobial resistance in reclaimed water by UV/NaClO: Simultaneous removal of ampicillin, blaNDM-1-carrying super-resistant bacteria and blaNDM-1 genes - Qiao Ma; Yingying Wang; Weiye Shi; Xintong Zhang; Yan Wang; Qian Li; Baoyu Gao; Defang Ma (Journal of Water Process Engineering, 2025)

The evolution of Fe5C2 with the carburization of N- and K-modified Fe/Fe3C core-shell catalysts during Fischer-Tropsch synthesis - Xuemei Shen; Chang Li; Yishuang Wang; Mingqiang Chen; Quan Wang; Defang Liang; Chunyue Cheng; Jun Wang (Chemical Engineering Journal, 2025)

Computer-driven formulation development of Ginsenoside Rh2 ternary solid dispersion - Tianshu Lu; Tongchuan Wu; Hao Zhong; Xue Li; Yunsen Zhang; Hao Yue; Yulin Dai; Haifeng Li; Defang Ouyang (Drug Delivery and Translational Research, 2025)

Exploring a novel toxicological mechanism: Ammonia-N induces neurotoxicity, oxidative damage in brain tissue, and modulates the expression of central appetite factors to suppress feeding in juvenile Siberian sturgeon (Acipenser baerii Brandt) - Xin Zhang; Qiang Hu; Huimin Sun; Jun Li; Ruitian Xiang; Tonglei Chen; Shuhuang Chen; Youlian Liu; Peng Tang; Ni Tang; Zhiqiong Li; Defang Chen (Aquaculture, 2025)

Effect of cortisol through GR regulated inflammatory cytokine expression and apoptosis of Siberian sturgeon (Acipenser baerii) after LPS treatment - Peng Tang; Hao Zhu; Defang Chen; Yinqiu Chen; Shuhuang Chen; Youlian Liu; Xin Zhang; Xiaoli Huang; Zhiqiong Li; Ping Ouyang; Yi Geng (Aquaculture, 2025)

Isolation, identification and histopathological observation of Francisella noatunensis subsp. orientalis from Nile tilapia (Oreochromis niloticus) - Ming Xu; Fulong Li; Baipeng Chen; Yongqiang Deng; Defang Chen; Yi Geng; Ping Ouyang; Xiaoli Huang (Aquaculture, 2025)

Pathological and molecular characteristics of a new infectious Streptococcus agalactiae from farmed Schizopygopsis pylzovi in southern China - Baipeng Chen; Ming Xu; Fulong Li; Zao He; Ping Ouyang; Defang Chen; Yi Geng; Xiaoli Huang (Aquaculture, 2025)

Localized heating coupling with radical oxidation eliminating antibiotic resistance genes (ARGs) in interfacial photothermal Fenton-like disinfection process - Haozheng Hou; Dingli Zou; Weiye Shi; Yingying Wang; Defang Ma; Yan Wang; Qian Li; Yue Gao; Baoyu Gao (Science of The Total Environment, 2024)

Synergistic singlet oxygen and UV irradiation for efficient intracellular ARGs removal via peroxymonosulfate/catalytic membrane-UV system - Xuan Hou; Yunxin Zhang; Min Wang; Jiajun Lu; Defang Ma; Qian Li; Ling Li; Zhining Wang; Baoyu Gao; Yan Wang (Journal of Hazardous Materials, 2024)

Residue behavior and quality influence of tolfenpyrad and cyromazine in cowpea during simulated household washing process - Shufan Jiang; Haoyue Li; Xuan Zhu; Shuhuai Li; Mingyue Wang; Defang Xie; Bei Li; Qiong Wu; Xinzhong Zhang; Bingjun Han (Food Control, 2024)

Synergistic role of phenylpropanoid biosynthesis and citrate cycle pathways in heavy metal detoxification through secretion of organic acids - Jing Guan; Yixin Zhang; Defang Li; Qinghua Shan; Zhangli Hu; Tuanyao Chai; Aimin Zhou; Kun Qiao (Journal of Hazardous Materials, 2024)

Histopathology and transcriptome profiling reveal features of immune responses in gills and intestine induced by Spring viremia of carp virus - Ping Ouyang; Qiunan Li; Shuya Liu; Yankai Li; Shuhan Li; Yongheng Zhou; Peng jia; Defang Chen; Xiaoli Huang; Yi Geng (Fish & Shellfish Immunology, 2024)

The dominant-substrate driven the enhanced performance in co-digestion of Pennisetum hybrid and livestock waste - Lintong Zhong; Fan Lin; Defang Wo; Xin Yang; Yongming Sun; Xidan Feng; Lianhua Li (Journal of Environmental Management, 2024)

In situ mass spectrometry imaging reveals pesticide residues and key metabolic pathways throughout the entire cowpea growth process - Shufan Jiang; Jingling Lin; Rui Zhang; Qiong Wu; Hongxing Li; Qun Zhang; Mingyue Wang; Longjun Dai; Defang Xie; Yue Zhang; Xinzhong Zhang; Bingjun Han (Journal of Hazardous Materials, 2024)

Predicting soil organic carbon content using simulated insitu spectra and moisture correction algorithms in southern Xinjiang, China - Peimin Yang; Yu Wang; Bifeng Hu; Shuo Li; Songchao Chen; Defang Luo; Jie Peng (Geoderma Regional, 2024)

Neglected function of gastrin to reduce feeding in Siberian sturgeon (Acipenser baerii) via cholecystokinin receptor B - Shupeng Zhang; Yongpei Lu; Yanling Liu; Mei Wang; Shaoqi Xu; Ya Li; Hongwei Wu; Qaolin Pei; Lei Yang; Lu Lu; Yixiao Xiong; Youlian Liu; et al. (Fish Physiology and Biochemistry, 2024)

Oxygen-containing functional groups in Fe3O4@three-dimensional graphene nanocomposites for enhancing H2O2 production and orientation to 1O2 in electro-Fenton - Yi Chen; Ruidian Su; Fei Xu; Mengyu Ma; Yan Wang; Defang Ma; Qian Li (Journal of Hazardous Materials, 2024)

Long-term dietary exposure to 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47) reduced feeding in common carp (Cyprinus carpio): Via the JAK-STAT signaling pathway - Xin Zhang; Youlian Liu; Huimin Sun; Shuhuang Chen; Peng Tang; Qiang Hu; Mengxuan He; Ni Tang; Zhiqiong Li; Defang Chen (Environmental Pollution, 2024)

Attapulgite-based MCM-41 zeolite supported Ni-Nb catalysts for hydrogen production by acetic acid steam reforming - Mingqiang Chen; Chuanlong Chen; Yishuang Wang; Defang Liang; Jinheng Yao; Lulu Shen; Haosheng Xin; Chang Li (Fuel, 2024)

Identification, characterization and the inflammatory regulating effect of NOD1/2 in sturgeon - Defang Chen; Hao Zhu; Lu Lu; Yinqiu Chen; Xin Zhang; Xiaoli Huang; Ping Ouyang; Yi Geng; Zhiqiong Li (Fish & Shellfish Immunology, 2024)

Salvia miltiorrhiza polysaccharide promotes the health of crayfish (Procambarus clarkii) by promoting hemocyte phagocytosis, protecting hepatopancreas and enhancing intestinal barrier function - Qiaolin Pei; Mengxuan He; Peng Tang; Xin Zhang; Xiaoli Huang; Xiaoli Zhang; Jiangyong Yang; Zhiqiong Li; Liangyu Li; Defang Chen (Fish & Shellfish Immunology, 2024)

Genotype diversity and antibiotic resistance risk in Aeromonas hydrophila in Sichuan, China - Kun Peng; Mengzhu Chen; Yilin Wang; Ziqi Tian; Longjun Deng; Tiancai Li; Yang Feng; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Brazilian Journal of Microbiology, 2024)

Cinnamaldehyde treats largemouth bass non-lethal bacterial enteritis by regulating gut morphology, barrier, inflammation, microbiota and serum biochemistry - Ping Ouyang; Shuanghui Huang; Wenyan Wei; Jianing Wu; Yongheng Zhou; Shuhan Li; Qiunan Li; Yi Geng; Xiaoli Huang; Defang Chen; Lizi Yin (Aquaculture, 2024)

Chronic ammonia stress caused disorder of intestinal microbiota and damaged intestinal structure and function in yellow catfish (Pelteobagrus fulvidraco) - Lin Luo; Senyue Liu; Baipeng Chen; Fulong Li; Yongqiang Deng; Xiaoli Huang; Yi Geng; Ping Ouyang; Defang Chen (Aquaculture, 2024)

Brain-derived neurotrophic factor (BDNF) activates PI3K-AKT-mTOR signaling via hypothalamic TrkB receptors to reduce feeding in Siberian sturgeon (Acipenser baerii) - Shupeng Zhang; Yongpei Lu; Yingzi Li; Yanling Liu; Qin Yao; Qin Kang; Shuhuang Chen; Youlian Liu; Yixiao Xiong; Defang Chen; Xin Zhang; Ni Tang; et al. (Aquaculture, 2024)

The potential mechanism of concentrated mannan-oligosaccharide promoting goldfish’s (Carassius auratus Linnaeus) resistance to Ichthyophthirius multifiliis invasion - Senyue Liu; Ming Xu; Baipeng Chen; Fulong Li; Yongqiang Deng; Yufan Zhang; Gang Lin; Defang Chen; Yi Geng; Yangping Ou; Xiaoli Huang (Fish & Shellfish Immunology, 2024)

Hybrid nanoassembly indicating a synthetic lethality relationship induces mitotic catastrophe-mediated tumor elimination - Shunzhe Zheng; Guanting Li; Shuwen Fu; Nannan Wang; Han Qiao; Meng Li; Xuanbo Zhang; Kaiyuan Wang; Wei Sun; Chutong Tian; Zhonggui He; Defang Ouyang; et al. (Chemical Engineering Journal, 2024)

High starch diets attenuate the immune function of Micropterus salmoides immune organs by modulating Keap1/Nrf2 and MAPK signaling pathways - Hongli Liu; Baipeng Chen; Yanhao Cao; Yi Geng; Ping Ouyang; Defang Chen; Liangyu Li; Xiaoli Huang (Fish & Shellfish Immunology, 2023)

Building ecological civilization: the importance of promoting green investments by Chinese companies - Defang Ma; Liangwei Li; Jingyi Zhang (Environmental Science and Pollution Research, 2023)

Simultaneous removal of antibiotics and antibiotic resistant genes using a CeO2@CNT electrochemical membrane-NaClO system - Xiaoyu Ni; Xuan Hou; Defang Ma; Qian Li; Ling Li; Baoyu Gao; Yan Wang (Chemosphere, 2023)

Co-isolated bacteria from septicemia of female Siberian sturgeon broodstock: Lactococcus petauri resisting Aeromonas hydrophila infection - Defang Chen; Fei Yang; Lei Yang; Qiaolin Pei; Xin Zhang; Xiaoli Huang; Ping Ouyang; Zhiqiong Li; Yi Geng (Aquaculture, 2023)

Removing antibiotic resistance genes through the synergistic effect of hydroxyl radical and hypochlorite radical generated in a CeO2@CNT electrified membrane – NaClO system - Xiaoyu Ni; Yan Wang; Xuan Hou; Defang Ma; Yunxin Zhang; Qian Li; Baoyu Gao (Chemical Engineering Journal, 2023)

Ethanol steam reforming over attapulgite-based MCM-41 supported Ni-Ce-Zr catalyst for hydrogen production - Mingqiang Chen; Xiaoyang Feng; Yishuang Wang; Defang Liang; Chang Li; Zhonglian Yang; Jun Wang (Fuel, 2023)

Salvia miltiorrhiza polysaccharides enhance the antioxidant capacity and immune resistance of hybrid sturgeon (Acipenser baerii♀ × Acipenser schrenckii♂) against Streptococcus iniae infection - Defang Chen; Hao Zhu; Daiyu Chen; Lei Yang; Fei Yang; Qiaolin Pei; Yue He; Xin Zhang; Lianshi Qu; Tianqiang Liu; Yi Geng; Zhiqiong Li (Aquaculture International, 2023)

Physiologically Based Pharmacokinetic Modeling for Multiple Oral Administration Labetalol in Pregnant Women - Yudi Song; Wei Wang; Xinyang Liu; Jingsi Chen; Dunjin Chen; Xiaoyi Wang; Wei Li; Defang Ouyang (Pharmaceutical Research, 2023)

Spatio-temporal dynamic diversity of bacterial alkaline phosphatase phoD gene and its environmental drivers in sediments during algal blooms: A case study of shallow Lake Taihu - Tingxi Zhang; Jiaying Wang; Siqi Zhou; Youling Chen; Defang Li (Journal of Environmental Management, 2023)

Iron-fortified Anaerobic Co-digestion Performance of Kitchen Waste and Pennisetum Hybrid - Defang Wo; Guican Bi; Lianhua Li; Xiaoying Kong; Enchen Jiang; Jun Xie (BioEnergy Research, 2023)

The inactivation of antibiotic-resistant bacteria and the damage of antibiotic-resistant genes using an electrified carbon nanotube membrane-NaClO system - Yan Wang; Xiaoyu Ni; Xuan Hou; Defang Ma; Bo Zhang; Qian Li; Baoyu Gao (Chemical Engineering Journal, 2023)

Galanin, a central appetite factor, affects appetite signals in the hypothalamus and promotes feeding in Siberian sturgeon (Acipenser baerii Brandt) - Xin Zhang; Shuhuang Chen; Hongwei Wu; Zhengzhi Tian; Ni Tang; Youlian Liu; Peng Tang; Qiang Hu; Yingzi Li; Qin Kang; Defang Chen; Zhiqiong Li (Aquaculture, 2023)

Visible light-driven chlorite activation process for enhanced sulfamethoxazole antibiotics degradation, antimicrobial resistance reduction and biotoxicity elimination - Xiaoyang Song; Ruidian Su; Yanhua Wang; Yan Zhang; Baoyu Gao; Yan Wang; Defang Ma; Qian Li (Chemical Engineering Journal, 2023)

Description of the whole mitochondrial genome of Bhatia longiradiata (Hemiptera, Cicadellidae, Deltocephalinae: Drabescini) and phylogenetic relationship - Jikai Lu; Jiajia Wang; Defang Li; Xianyi Wang; Renhuai Dai (Genes & Genomics, 2023)

Identification and expression profiling of receptor‐interacting serine/threonine‐protein kinase 2 in Siberian sturgeon ( Acipenser baerii ) - Lu Lu; Shaotong Dai; Hao Zhu; Xin Zhang; Zhiqiong Li; Xiaoli Huang; Ping Ouyang; Yi Geng; Defang Chen (Journal of Fish Biology, 2023)
Receptor‐interacting serine/threonine‐protein kinase 2 (RIPK2) is an adaptor protein of the pattern recognition receptors NOD1 and NOD2 involved in regulating inflammatory response and resisting pathogenic microbial infection. In this study, Acipenser baerii RIPK2 ( AbRIPK2 ) was identified. The open reading frame of AbRIPK2 was 1815 bp encoding 604 amino acids. AbRIPK2 possessed the typical N‐terminal kinase domain (KD) and C‐terminal caspase recruitment domain (CARD). The phylogenetic tree analysis revealed that AbRIPK2 shared a relatively high identity with bony fish. Real‐time fluorescence quantitative PCR (qRT‐PCR) results indicated that AbRIPK2 was highly expressed in the gill, followed by muscle, liver and heart. AbRIPK2 was significantly induced in the spleen and valvular intestine after Streptococcus iniae and Aeromonas hydrophila infection. AbRIPK2 was significantly upregulated after peptidoglycan (PGN) treatment in the splenic leukocytes. This study indicated that AbRIPK2 played a potential role in resisting the pathogenic infection of Siberian sturgeon by responding to bacteria.

Comparative transcriptome and adaptive evolution analysis on the main liver and attaching liver of Pareuchiloglanis macrotrema - Qing Wu; Xiaoyang Zhang; Jie Li; Longjun Deng; Dongjie Wang; Min Liao; Zhonggang Guo; Xiaoli Huang; Defang Chen; Yan Wang; Shiyong Yang; Zongjun Du; et al. (Journal of Applied Genetics, 2022)

The insulin gene as an energy homeostasis biomarker in Yangtze sturgeon (Acipenser dabryanus) - Xin Zhang; Hu Chen; Ya Li; Ni Tang; Defang Chen; Zhiqiong Li (Fish Physiology and Biochemistry, 2022)

Cloning and expression of kiss genes and regulation of feeding in Siberian sturgeon (Acipenser baerii) - Shaoqi Xu; Mei Wang; Ya Li; Ni Tang; Xin Zhang; Hu Chen; Shupeng Zhang; Yanling Liu; Jun Wang; Defang Chen; Zhiqiong Li (Fish Physiology and Biochemistry, 2022)

The sub-inhibitory concentration of cinnamaldehyde resists Aeromonas hydrophila pathogenicity via inhibition of W-pili production - Ping Ouyang; Jiehao Chen; Lizi Yin; Yi Geng; Defang Chen; Kaiyu Wang; Weiming Lai; Hongrui Guo; Jing Fang; Zhengli Chen; Li Tang; Chao Huang; et al. (Aquaculture International, 2021)

Overexpression of CcNAC1 gene promotes early flowering and enhances drought tolerance of jute (Corchorus capsularis L.) - Gaoyang Zhang; Siqi Huang; Chao Zhang; Defang Li; Yingbao Wu; Jielou Deng; Shilian Shan; Jianmin Qi (Protoplasma, 2021)

Characterization, tissue distribution of resistin gene and the effect of fasting and refeeding on resistin mRNA expression in Siberian sturgeon ( Acipenser baerii ) - Ni Tang; Yanlin Liu; Zhengzhi Tian; Shaoqi Xu; Mei Wang; Hu Chen; Bin Wang; Ya Li; Yan Wang; Song Yang; Liulan Zhao; Defang Chen; et al. (Journal of Fish Biology, 2020)
Resistin as an adipokine identified from rodents in 2001 is involved in many biological processes. However, little is known about this gene in fish. We cloned Siberian sturgeon ( Acipenser baerii ) resistin cDNA of 795 base pairs, encoding 107 amino acids, which showed 38–40% identity to human and rodents. Real‐time quantitative PCR showed that the resistin gene was widely distributed in tissues of Siberian sturgeon, with the highest expression in liver. After fasting for 1, 3, 6 and 10 days, the expression of the resistin gene in the liver of Siberian sturgeon decreased significantly, and after refeeding on the 10 days of fasting the resistin mRNA expression increased rapidly, suggesting that resistin may play an important role in liver in response to starvation. Taken together, these results suggest that resistin may be involved in the regulation of energy homeostasis in liver.

Physiological responses and tolerance of flax (Linum usitatissimum L.) to lead stress - Gen Pan; Lining Zhao; Jianjun Li; Siqi Huang; Huijuan Tang; Li Chang; Zhigang Dai; Anguo Chen; Defang Li; Zheng Li; Yong Deng (Acta Physiologiae Plantarum, 2020)

Genome-wide development of simple sequence repeats database for flax (Linum usitatissimum L.) and its use for genetic diversity assessment - Gen Pan; Anguo Chen; Jianjun Li; Siqi Huang; Huijuan Tang; Li Chang; Lining Zhao; Defang Li (Genetic Resources and Crop Evolution, 2020)

Outbreak of carp edema virus disease in cultured ornamental koi in a lower temperature in China - Ping Ouyang; Yaojia Zhou; Ruixue Yang; Zhuangzhi Yang; Kaiyu Wang; Yi Geng; Weiming Lai; Xiaoli Huang; Defang Chen; Jing Fang; Zhengli Chen; Li Tang; et al. (Aquaculture International, 2020)

GSK3β inhibition suppresses the hepatic lipid accumulation in Schizothorax prenanti - Yan Wang; Xiaochen Zhan; Wei Luo; Liulan Zhao; Song Yang; Defang Chen; Zhiqiong Li; Linjie Wang (Fish Physiology and Biochemistry, 2019)

Insight into the Dissolution Molecular Mechanism of Ternary Solid Dispersions by Combined Experiments and Molecular Simulations - Run Han; Tianhe Huang; Xinyang Liu; Xunqing Yin; Haifeng Li; Jiahong Lu; Yuanhui Ji; Huimin Sun; Defang Ouyang (AAPS PharmSciTech, 2019)

A Novel Biscarbazole-Xanthene Hybrid Fluorescent Probe for Selective and Sensitive Detection of Cu2+ and Applications in Bioimaging - Kun Huang; Defang Han; Xianglin Li; Mengni Peng; Qi Qiu; Dabin Qin (Journal of Fluorescence, 2019)

Full genome sequence of the first bluetongue virus serotype 21 (BTV-21) isolated from China: evidence for genetic reassortment between BTV-21 and bluetongue virus serotype 16 (BTV-16) - Shaomin Qin; Heng Yang; Yixuan Zhang; Zhanhong Li; Jun Lin; Lin Gao; Defang Liao; Yingying Cao; Pengfei Ren; Huachun Li; Jianmin Wu (Archives of Virology, 2018)

One evidence of cocaine- and amphetamine-regulated transcript (CART) has the bidirectional effects on appetite in Siberian sturgeon (Acipenser baerii) - Xin Zhang; Yundi Gao; Ni Tang; Jinwen Qi; Yuanbing Wu; Jin Hao; Shuyao Wang; Defang Chen; Zhiqiong Li (Fish Physiology and Biochemistry, 2018)

Erratum to: CX3CR1 deficiency accelerates the development of retinopathy in a rodent model of type 1 diabetes - Eleni Beli; James M. Dominguez; Ping Hu; Jeffrey S. Thinschmidt; Sergio Caballero; Sergio Li Calzi; Defang Luo; Sumathi Shanmugam; Tatiana E. Salazar; Yaqian Duan; Michael E. Boulton; Susanna Mohr; et al. (Journal of Molecular Medicine, 2017)

Integration of coagulation and adsorption for removal of N-nitrosodimethylamine (NDMA) precursors from biologically treated municipal wastewater - Miaomiao Wang; Yingjie Meng; Defang Ma; Yan Wang; Fengli Li; Xing Xu; Chufan Xia; Baoyu Gao (Environmental Science and Pollution Research, 2017)

RNA-seq for comparative transcript profiling of kenaf under salinity stress - Hui Li; Defang Li; Anguo Chen; Huijuan Tang; Jianjun Li; Siqi Huang (Journal of Plant Research, 2017)

Design and Evaluation of Hydrophilic Matrix System Containing Polyethylene Oxides for the Zero-Order Controlled Delivery of Water-Insoluble Drugs - Lijie Wang; Kai Chen; Haoyang Wen; Defang Ouyang; Xue Li; Yunyun Gao; Weisan Pan; Xinggang Yang (AAPS PharmSciTech, 2017)

CX3CR1 deficiency accelerates the development of retinopathy in a rodent model of type 1 diabetes - Eleni Beli; James M. Dominguez; Ping Hu; Jeffrey S. Thinschmidt; Sergio Caballero; Sergio Li Calzi; Defang Luo; Sumathi Shanmugam; Tatiana E. Salazar; Yaqian Duan; Michael E. Boulton; Susanna Mohr; et al. (Journal of Molecular Medicine, 2016)

Reduction of disinfection by-product precursors in reservoir water by coagulation and ultrafiltration - Feng Wang; Baoyu Gao; Defang Ma; Qinyan Yue; Ruihua Li; Qianwen Wang (Environmental Science and Pollution Research, 2016)

Molecular characterization of melanin-concentrating hormone (MCH) in Schizothorax prenanti: cloning, tissue distribution and role in food intake regulation - Tao Wang; Dengyue Yuan; Chaowei Zhou; Fangjun Lin; Rongbin Wei; Hu Chen; Hongwei Wu; Zhiming Xin; Ju Liu; Yundi Gao; Defang Chen; Shiyong Yang; et al. (Fish Physiology and Biochemistry, 2016)

Complete genome sequence of a Chuzan virus strain isolated for the first time in mainland China - Heng Yang; Lei Xiao; Jinxing Meng; Heli Xiong; Lin Gao; Defang Liao; Huachun Li (Archives of Virology, 2016)

Ya-fish (Schizothorax prenanti) spexin: identification, tissue distribution and mRNA expression responses to periprandial and fasting - Hongwei Wu; Fangjun Lin; Hu Chen; Ju Liu; Yundi Gao; Xin Zhang; Jin Hao; Defang Chen; Dengyue Yuan; Tao Wang; Zhiqiong Li (Fish Physiology and Biochemistry, 2016)

Effects of operating conditions on trihalomethanes formation and speciation during chloramination in reclaimed water - Fang Wang; Baoyu Gao; Defang Ma; Ruihua Li; Shenglei Sun; Qinyan Yue; Yan Wang; Qian Li (Environmental Science and Pollution Research, 2016)

Complete genome sequence of the first bluetongue virus serotype 7 isolate from China: evidence for entry of African-lineage strains and reassortment between the introduced and native strains - Heng Yang; Minna Lv; Minfei Sun; Liqin Lin; Meilin Kou; Lin Gao; Defang Liao; Heli Xiong; Yuwen He; Huachun Li (Archives of Virology, 2016)

Identification and characterization of the RCI2 gene family in maize (Zea mays) - YANG ZHAO; HAIQING TONG; RONGHAO CAI; XIAOJIAN PENG; XIAOYU LI; DEFANG GAN; SUWEN ZHU (Journal of Genetics, 2014)

Genome-wide detection of genetic loci triggering uneven descending of gametes from a natural hybrid pine - Shuxian Li; Zaixiang Tang; Defang Zhang; Ning Ye; Chenwu Xu; Tongming Yin (Tree Genetics & Genomes, 2012)

N and O isotopes and the ore-forming mechanism of nitrate deposits in the Turpan-Hami Basin, Xinjiang, China - Yan Qin; YanHe Li; Feng Liu; KeJun Hou; DeFang Wan; Cheng Zhang (Science China Earth Sciences, 2012)